Pengelolaan Kawasan Ekonomi Khusus Sei Mangkei Berbasis Penilaian Kinerja Lingkungan - Nobrya Husni (Inovasi, 2018)
Major business in the Special Economic Zone (SEZ) Sei Mangkei is a palm oil and rubber processing industry, with supporting businesses such as logistics, energy, electronics, production support industries, various industries, and tourism. The products produced are: fatty acid, fatty alcohol, surfactant, biodiesel, and biogas (National Council of KEK, 2015). Operational activities in the industrial area provide benefits from economic aspects, but on the other hand generate waste, so it can be said that the environment and operational activities have a relationship. Therefore, important environmental considerations as an effort to reduce environmental damage to minimize the risk of environmental damage and still gain a profit. This study aims to determine the understanding of managers and tenants on the assessment of environmental performance, especially from environmental aspects, and analyzing SEZ Sei Mangkei's readiness in conducting environmental performance assessment from environmental aspect. The research was conducted by survey method with data collection technique through interview and questionnaire. Data analysis is done quantitatively descriptive and qualitative. Based on the result of the research, it is concluded that the managers and tenants of KEK Sei Mangkei have good understanding on the concept of environmental performance assessment based on ISO 14031.on the concept of environmental performance assessment based on ISO 14031. Keywords: special economic zone, oil palm, ISO 14031, environment indicators